Perceptions of Teachers and Students on Extracurricular Activities - Bhusal, Yagya Prasad (Shaheed Smriti Journal, 2024)
This study investigates the perceptions of teachers and students regarding extracurricular activities in schools within Khairahani Municipality, Chitwan district. The aim is to understand how these activities are perceived and valued at the school level. The municipality hosts 51 schools, including 21 secondary schools and 30 basic schools. A total of 102 respondents, consisting of 51 teachers and 51 students, participated in the study, selected through a simple random sampling method. Following a positivist research paradigm, the study employed a quantitative survey approach. Data were collected through structured questionnaires administered in schools and analyzed using SPSS software. The analysis focused on frequencies and percentages to identify key trends and insights. The findings provide a deeper understanding of the value and impact of extracurricular activities in the educational context of Khairahani Municipality.